19 Years Old Male Patient with Cholelithiasis: A Case Report - Semara, Putu Bagus Aditya Putra; Wirawan, I Made Suma (Indonesian Health Journal, 2024)
Cholelithiasis refers to the formation of hardened deposits of digestive fluid, known as gallstones, which can develop in the gallbladder, bile duct, or both. This study aims to analyze the factors contributing to the occurrence of cholelithiasis in young patients, specifically 19-year-old males, and identify the clinical symptoms and associated examination results. A 19-year-old male patient visited the Internal Medicine Polyclinic with the main complaint of right upper abdominal pain radiating to the back. He also experienced nausea and vomiting. The patient frequently consumed high-fat foods. On physical examination, the patient's height was 171 cm, weight 74 kg, and BMI 25.34 kg/m² (overweight). Abdominal examination revealed a positive Murphy's sign. Laboratory tests showed total cholesterol of 216 mg/dl, LDL 158 mg/dl, HDL 38 mg/dl, and triglycerides 86 mg/dl. An abdominal ultrasound indicated thickened gallbladder walls, a single stone measuring approximately 0.82 cm by 1.17 cm, accompanied by sludge, and calcification in the right lobe of the liver. The patient was treated with Ursodeoxycholic Acid (UDCA) 250 mg twice daily and Atorvastatin 10 mg once daily.   Cholelithiasis is a multifactorial condition, influenced by several factors, commonly referred to as the "4F" factors: female gender, age over 40, fertility (being in the fertile period), and fat (obesity). Other contributing factors include age, genetics, and race. Children and adolescents may develop gallstones due to increased consumption of fat, refined carbohydrates, and low fiber intake. Overweight and obesity are significant risk factors because they increase the secretion of intrahepatic cholesterol, which promotes gallstone formation. The treatment of cholelithiasis can be classified into non-surgical and surgical approaches.